PABRIK HYDROLIZED POLYACRYLAMIDE DARI MONOMER ACRYLAMIDE KAPASITAS 40.000 TON/ TAHUN - , NICKO ANANDA; , Budhijanto, ST, MT., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In general, the production of Hydrolized Polyacrylamide (HPAM) comprises two steps, polymerization process of acrylamide monomer to produce polyacrylamide and hydrolysis of polyacrylamide to produce HPAM. The operating condition for polymerization process is at 60 oC and 1 atm. The total conversion of acrylamide in the polymerization reaction is 90% to acrylamide. Furthermore, polyacrylamide is hydrolyzed using KOH as the hydrolyzing agent at 60 oC and 1 atm. The conversion of polyacrylamide is 30%. The design capacity of HPAM plant is 40,000 tons/year. To produce 40,000 tons/year of HPAM with 98% mass of purity, 400084 tons/year of acrylamide, 13,898 tons/year of methanol, 31.68 tons/year of K2S2O8, 3,413 tons/year of KOH, and 522 kg/year of hydroquinone are needed for the process. The plant will be established in Cilegon, Banten with a total area of 50,000 m2, it requires 200 workers. In addition, the plant is supported by utility facility requiring 594,583.693 kg/hr of water and 891.15 KW of electricity. To establish the plant, the economic evaluation should be considered first. Economic evaluation resulted in the economic feasibility parameters as follow: Fixed Capital Investment (FCI) of Rp 328,776,577,346.65 and US$ 21,628,359.33